Position and retention in gyms and health clubs - Gonçalves, Celina (2014)
Physical exercise is no longer seen only as leisure but it has also become a need to wellbeing, health promotion, stress reduction and obesity combating. Other reasons are added, which are related to harmony, body cult, aesthetics, ageing delay and emotional rebalance – concept of wellness diffused in Gyms and Health Clubs. These must permanently interact with the members in their constant maintenance – retention. The present poster will discuss the extent to which retention, within the context of Gyms and Health Clubs, is an influence through the members’ perception and how does that perception influence the member to stay. A qualitative and quantitative method will be used by means of interview and questionnaire. In the qualitative analysis the content analysis will be used and in the quantitative analysis the descriptive and inferential statistics.